2016
DOI: 10.1016/j.neuroimage.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Neural networks for harmonic structure in music perception and action

Abstract: 1The ability to predict upcoming structured events based on long-term knowledge and 2 contextual priors is a fundamental principle of human cognition. Tonal music triggers 3 predictive processes based on structural properties of harmony, i.e., regularities defining the 4 arrangement of chords into well-formed musical sequences. While the neural architecture of 5 structure-based predictions during music perception is well described, little is known about 6 the neural networks for analogous predictions in musica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 75 publications
6
41
0
2
Order By: Relevance
“…These results suggest that, in addition to the right STG/MTG, the right IFG-MFG-PreCG appears to be another crucial hub in acquired amusia as its lesions and atrophy are linked to initial severity and poor recovery. Previously, these areas have been implicated in the sequencing of auditory information and structural (syntactic) analysis of music (Koelsch, 2005; Tillmann et al, 2006; Bianco et al, 2016) in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that, in addition to the right STG/MTG, the right IFG-MFG-PreCG appears to be another crucial hub in acquired amusia as its lesions and atrophy are linked to initial severity and poor recovery. Previously, these areas have been implicated in the sequencing of auditory information and structural (syntactic) analysis of music (Koelsch, 2005; Tillmann et al, 2006; Bianco et al, 2016) in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in the domains of language, music, and vision have investigated the discrimination of hierarchical structures by asking participants to evaluate whether sequences of items are well‐formed according to a previously learned system of rules (Bahlmann, Schubotz, & Friederici, ; Bahlmann, Schubotz, Mueller, Koester, & Friederici, ; Bianco et al, ; Friederici, Bahlmann, Friedrich, & Makuuchi, ; Maess, Koelsch, Gunter, & Friederici, ; Sammler, Koelsch, & Friederici, ). These studies suggest that lateral prefrontal cortex (PFC, particularly inferior frontal gyrus, IFG) might contribute multi‐domain resources to the processing of hierarchies (Fadiga, Craighero, & D'Ausilio, ; Friederici et al, ; Patel, ), in interaction with areas along ventral visual/auditory streams that may store domain‐specific schematic information (Bianco et al, ; Martins et al, ; Oechslin, Gschwind, & James, ; Pallier, Devauchelle, & Dehaene, ; Sammler et al, ). Recent anatomical research has shown that IFG in humans is expanded (Schenker et al, ) and more strongly connected with the posterior temporal regions in comparison to other primates (Neubert, Mars, Thomas, Sallet, & Rushworth, ; Rilling et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This pre-Drop delay, including rising musical features, may cause greater tension associating with enhanced PCUN activity (Vuilleumier & Trost, 2015). As musical features deviate post-Drop, this heightened tension may amplify positive emotions due to contrastive valence, as well as mediating IFG and MFG activity (Bianco et al, 2016;Lappe et al, 2013;Seger et al, 2013). Therefore, Drops' tension-inducing and deviating structure may link to ITPRA via tension and prediction, which may also mediate activity in the PCUN pre-Drop and IFG and MFG post-Drop, as well as being associated with greater arousing and positive emotions, including excitement.…”
Section: Linking Drop Structure Brain Activity and Emotionsmentioning
confidence: 99%
“…Music follows certain structures or rules within time, musical events, intensity and space, enabling musical syntax which is associated with IFG activity (Asano & Boeckx, 2015;Lehne et al, 2014;Koelsch, 2014;Kunert et al, 2015). Musical syntax facilitates predictability and listeners' anticipation of future music moments, which relates to musical tension, positive emotions when predictions are correct, and co-occurring IFG activity (Bianco et al, 2016;Huron, 2006;Koelsch, 2014;Lehne et al, 2014;Schön et al, 2010;Zatorre, Chen, & Penhune, 2007). Thus, the ITPRA theory suggests music evokes emotions via tension and anticipation of predicted moments, and tension has been shown to relate to IFG activity.…”
Section: Linking Drop Structure Brain Activity and Emotionsmentioning
confidence: 99%
See 1 more Smart Citation